The relationships between stress, stress-coping behaviors, and suicidal risk among Thais who had become unemployed due to the COVID-19 pandemic: A cross-sectional study - Chalermpon Kajai; Wanich Suksatan; Nittaya Promkunta; Natakorn Kamkaew (Belitung Nursing Journal, 2022)
Background: The COVID-19 pandemic has resulted in severe mental health problems worldwide. Thus, in addition to the high number of people who have died from infection with complications, some have committed suicide. Objective: This study aimed to determine the relationships between stress, stress-coping behaviors, and suicidal risk among those who had become unemployed in Thailand due to the COVID-19 pandemic. Methods: This study had a cross-sectional correlational design and included 447 unemployed Thais at least 18 years of age who had become unemployed due to the COVID-19 pandemic. The participants were selected through multistage sampling. A self-administered questionnaire was used for data collection. The data were then analyzed using frequency, percentage, and Spearman’s correlation coefficient. Results: Most participants had moderate-level stress (73.16%) and stress-coping behaviors (71.81%). Almost all the participants had no suicidal risk (76.73%). The stress level and overall stress-coping behavior were positively correlated with suicidal risk (r = 0.305, p <0.01 and r = 0.352, p <0.01, respectively). Conclusion: Stress and stress-coping behaviors were associated with suicidal risk among Thais who had become unemployed due to the COVID-19 pandemic. Hence, nurses must screen patients with psychological problems, especially those who have become unemployed due to the COVID-19 pandemic, for suicide risk. Developing interventions to reduce such patients’ stress and promote appropriate stress-coping behaviors is essential.